2022
DOI: 10.3389/fnut.2022.780003
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Prevalence and Nutrient Intakes of Indonesian Community-Dwelling Older Adults: A Systematic Review of Observational Studies

Abstract: BackgroundMalnutrition and inadequate nutrient intake are associated with functional decline, frailty, and bad clinical outcomes among community-dwelling older adults. Despite the growing proportion of the elderly population in Indonesia, data on the prevalence of malnutrition and adequacy of macronutrient and micronutrient intakes among Indonesian older adults are scattered and vary between studies. Therefore, our study aims to obtain data on malnutrition prevalence, level and distribution of nutrient intakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Younger adults likely have better intrinsic nutrient status and resilience compared to midlife women ( 64 ). Optimizing MN intake could help compensate for age-related changes and counteract sarcopenic progression in midlife women ( 65 ). These results provide implications for tailoring MN intake recommendations by specific life stages and conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Younger adults likely have better intrinsic nutrient status and resilience compared to midlife women ( 64 ). Optimizing MN intake could help compensate for age-related changes and counteract sarcopenic progression in midlife women ( 65 ). These results provide implications for tailoring MN intake recommendations by specific life stages and conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study emphasize the potential benefits of educational interventions in improving nutritional status in community-dwelling older adults and potentially mitigating the adverse consequences linked to frailty, irrespective of their age, sex, physical frailty status, and educational background. This is an interesting result, particularly given the association of malnutrition with age ( 56 ). The observed improvement, irrespective of the participants’ age or other potential covariates such as educational status (which could be linked to a better understanding of the intervention), indicates that the FRAGSALUD intervention is an effective program for reducing the risk of malnutrition in older adults living in the community.…”
Section: Discussionmentioning
confidence: 76%
“…According to BMI criteria, the prevalence of malnutrition in older patients ranged from 8.0 to 26.6%, based on a prior study conducted in Indonesia. In contrast, malnutrition was prevalent in 18-78% of the population with the MNA, while its frequency varied from 2.1-14.6% 19 . The study found that 46.5% of the elderly hospitalized in the study were malnourished, and 29.1% were at risk of malnutrition.…”
Section: Resultsmentioning
confidence: 84%